PERANCANGAN KEMASAN PRODUK YANG RAMAH LINGKUNGAN MENGGUNAKAN METODE GREEN QFD-II PADA PERUSAHAAN AMDK AL QODIRI - Handriyono Handriyono; Arnis Budi Susanto; Cyntia Oktavia Sundjojo (BISMA: Jurnal Bisnis dan Manajemen, 2021)
Bottled mineral water is a product that has experienced rapid development since decades ago. The human need for drinking water has influenced many companies in establishing the bottled mineral water industry. Al Qodiri is one of the companies engaged in the bottled mineral water industry. The development of the bottled mineral water industry currently has impacts on the environment. Global warming is the main effect of plastic bottle waste that cannot be decomposed for hundreds of years. This study proposes the packaging improvement of Al Qodiri bottled mineral water (600 ml) based on customer needs, environmentally friendly, and economical cost. The data analysis method applied in this study was the Green Quality Function Deployment-II. The sampling methods used in this study were non-probability sampling and convenience sampling techniques. The results showed that Al Qodiri bottled mineral water products need to redesign their packaging and use recycled PET as new raw materials for packaging. Therefore, the raw material costs will be reduced by Rp 72,000 every day and Rp 26,280,000 every year. Keywords: Green QFD-II, customer needs, green packaging, quality